Bright's Disease, Malaria, and Machine Politics: The Story of the Illness of President Chester A. Arthur - Pappas, Theodore N. (The Surgery Journal, 2017)
In July of 1881, President James A. Garfield was shot in the back at the Sixth Street Train Station in Washington, D.C. Garfield died after an extended illness and Chester A. Arthur assumed the presidency on September 20, 1881. He served the remaining three and a half years but was ill for most of his term. Arthur died of the complications of Bright's disease less than two years after leaving office. In the 1880s, Bright's disease was the syndrome that described renal failure associated with proteinuria, but the etiology of Arthur's kidney failure has never been determined. Arthur is one of our least understood Presidents, owing to his brief tenure in office, his death shortly after leaving office, and the fact that he burned all his personal papers just prior to his death. This manuscript will explore the medical history of Chester A. Arthur, including his presumed diagnosis of malaria, his symptoms during his declining health, and will define the differential diagnosis of the causes of his renal failure that culminated in his death in November of 1886.
Keywords: Chester A. Arthur; Bright's disease; malaria; renal failure